The outcome of acute leukemia patients with SET-NUP214 fusion after allogeneic stem cell transplantation - Shen, Yuyan; Yang, Donglin; Zhang, Rongli; Chen, Xin; Ma, Qiaoling; Wei, Jialin; Zhai, Weihua; Pang, Aiming; He, Yi; Jiang, Erlie; Feng, Sizhou (Frontiers in Oncology, 2023)
SET-NUP214 fusion gene (also known as TAF-1-CAN and SET-CAN) is observed in acute myeloid leukemia (AML) and T-cell lymphoblastic leukemia (T-ALL). SET-NUP214 fusion in T-cell lymphoblastic leukemia is associated with chemotherapy resistance, but the prognosis of AML patients with SET-NUP214 is rarely reported. We here retrospectively analyze all acute leukemia including AML and T-ALL patients with SET-NUP214 fusion who underwent allogeneic stem cell transplantation (alloHSCT) in our center from July 2017 to Nov 2022. Of the total 11 patients, 5 patients are diagnosed with AML, 6 patients are diagnosed with T-ALL de novo. All patients receive myeloablative regimens in CR1, 3 (60%) AML patients relapsed post alloHSCT, and 3 T-ALL (50%) patients relapsed post alloHSCT. Only 1 AML patient relapsed post alloHSCT respond to subsequent chemotherapy plus donor lymphocyte infusion and survived to the last follow-up. The estimated 1-year overall survival and 3-year overall survival for all these 11 patients are 69.3% and 38.5%, respectively. The estimated 1-year leukemia-free survival and 3-year leukemia-free survival for all patients are 69.3% and 38.5%, respectively. The research shows high incidence of relapse for acute leukemia patients with SET-NUP214 fusion gene, even after alloHSCT. More clinical trials or researches with larger samples are in urgent need for this group of patients.